RURAL EMPLOYMENT STRATEGY: PROBLEMS AND SOLUTIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The article considers the main goals, directions, tasks, mechanisms and factors of effective and comprehensive use of available labor resources and reduction of unemployment in rural areas in a particular region of the Republic of Uzbekistan. In the developed and proposed strategy for the development of the rural labor market, the main market criteria and quantitative statistical indicators for assessing, analyzing and predicting the promising state of the labor market are proposed.